KONTRIBUSI PENDEKATAN PEMBELAJARAN KONSTRUKTIVISME DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PAI DI SEKOLAH - Abdurrahmansyah A (Universitas Islam Negeri Raden Fatah Palembang, 2014)
Abstract The methodological problem on Islamic Religion Education learning (PAI) at schools is still laid on direct learning so that it is hard to build students' critical thinking. Constructivistik approach using cooperative learning, problem solving, and inquiry model can be used on PAI learning in terms of constructing students' thinking in order that students are openly able to act and behave to realities taking place in society. Cooperative model is effective enough to construct tolerance among students. Religion learning correlated to active learning can develop morality aspects and religion values such as honesty, care, responsibility, discipline, and interaction.   Keywords: Islamic education, active learning, constructivistik, morality.